(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The 21st centuries’ growth in various sectors has led our country towards achieving the distinction of one of the growing nations in the world. Various efforts have been made by the Government as well as Non Government Organizations but the literacy rate is increased if we compare it with the few decades back, but the cent percent literacy is not achieved till today. The literacy rate of the disadvantaged community is still poor. In Andhra Pradesh, in spite of the various constitutional safeguards and all the different schemes by the state government, literacy level of the disadvantaged group is found to be much lower than that of the rest of the society. This may caused by the various factors. Among these factors, socio-economic statuses, parental attitude, their interest to give education to their children, their awareness regarding education and so on play a vital role. While parents of the disadvantaged children are not highly in favour of schooling and education of their children, today’s scenario might have improved with widespread awareness regarding value of education. In this context, it is imperative to evaluate the perceptions and attitude of these parents.